2012
DOI: 10.1093/aob/mcs119
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mangiferin and hydroxycinnamic acid ester accumulation in coffee (Coffea) leaves: biological implications and uses

Abstract: This survey of the phenolic composition in Coffea leaves shows that mangiferin and HCE accumulation corresponds to lineage recognition and species delimitation, respectively. Knowledge of the spectrum of phenolic accumulation within species and populations could be of considerable significance for adaptation to specific environments. The potential health benefits of coffee-leaf tea, and beverages and masticatory products made from the fleshy parts of Coffea fruits, are supported by our phenolic quantification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 77 publications
13
109
0
2
Order By: Relevance
“…To date, phenol histolocalization is generally done using Neu's reagent, which binds with phenolics, emitting a specific greenish-white epifluorescence under UV light (Neu, 1956). As expected, the most intense greenish-white fluorescence is observed in juvenile coffee leaf blades (Mondolot et al, 2006; Campa et al, 2012), but its specificity toward HQA is low. By contrast, mangiferin histolocalization by epifluorescence does not require any reagents and has been directly observed through its autofluorescence (Talamond et al, 2011; Campa et al, 2012).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…To date, phenol histolocalization is generally done using Neu's reagent, which binds with phenolics, emitting a specific greenish-white epifluorescence under UV light (Neu, 1956). As expected, the most intense greenish-white fluorescence is observed in juvenile coffee leaf blades (Mondolot et al, 2006; Campa et al, 2012), but its specificity toward HQA is low. By contrast, mangiferin histolocalization by epifluorescence does not require any reagents and has been directly observed through its autofluorescence (Talamond et al, 2011; Campa et al, 2012).…”
Section: Introductionsupporting
confidence: 67%
“…CQA and diCQA are indeed the most abundant soluble hydroxycinnamic acids (HQA) present in leaves and seeds (Clifford, 1985; Ky et al, 2001; Campa et al, 2012). Three isomers occur in each class according to the acylating residue positions, but the most important in terms of content is 5- O -caffeoylquinic acid, more commonly known as chlorogenic acid (Clifford, 1985) (see Figure A in supplementary material).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, many research papers presented that the phenolic compounds were the good free radical scavenger. In addition, previous studies showed that coffee bean contained many polyphenolic compounds such as chlorogenic acid, mangiferin and hydroxycinnamic acid esters (Vignoli et al, 2011;Campa et al, 2012;Moreira et al, 2013). The major phenolic acid in all coffee samples was chlorogenic acid (Cheong et al, 2013).…”
Section: Determination Of Total Phenolic Contentmentioning
confidence: 84%
“…62 Under irrigation or not, extracts from coffee leaves presented a band around 1665 cm -1 as important variable. This band is characteristic of the presence of the carbonyl group, for which this region may indicate the presence of several compounds such as proteins, 55 caffeine, 6,30 ketone between two aromatic rings 62 as in xanthone structures found in the form of mangiferin detected in coffee leaves, 7 among others. Bands indicated by loadings between 1100 and 1000 cm -1 are possibly C-O stretches of carbohydrates.…”
Section: Resultsmentioning
confidence: 98%
“…However, there is relatively little research carried out on metabolites in other coffee plant parts, including the leaves. [7][8][9][10][11] Phenolic compounds found in the coffee leaves 7 have been shown to be potentially beneficial for health, although the influence of consumption of these compounds on the human body requires further research. Other metabolite groups are found in coffee leaves, such as alkaloids, 12 several carbohydrates 13,14 and lipids 9 among others.…”
Section: Introductionmentioning
confidence: 99%